THE PRACTICE OF MERARIQ (RELATED MARRIAGE) IN THE SASAK TRIBE, REVIEWED FROM A HUMAN RIGHTS PERSPECTIVE - Berliana Febia Bahtiar Motulo,; Muh. Jufri Ahmad, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to analyze the human rights foundation as a perspective for examining the practice of merariq (elopement) within the Sasak indigenous community. Merariq is a marital tradition where the prospective groom "takes" or "runs away with" the prospective bride, frequently without her explicit consent. The coercive elements and potential infringement upon fundamental individual rights render this practice legally contentious. Employing a normative juridical method through literature study, the research finds that merariq is often conducted under coercion and without the free consent of both parties, thereby constituting a human rights violation. Core human rights principles such as universality, equality, non-discrimination, and the indivisibility and interdependence of rights are also compromised. Furthermore, this practice contravenes several statutory provisions, including Law No. 1 of 1974 on Marriage as amended by Law No. 16 of 2019, and Law No. 39 of 1999 on Human Rights.